Transport activities and expression patterns of glycine transporters 1 and 2 in the developing murine brain stem and spinal cord - Lall, Deepti; Armbruster, Anja; Ruffert, Karelia; Betz, Heinrich; Eulenburg, Volker (Biochemical and Biophysical Research Communications, 2012)
Glycine serves as a neurotransmitter in spinal cord and brain stem, where it activates inhibitory glycine receptors. In addition, it serves as an essential co-agonist of excitatory N-methyl-d-aspartate receptors. In the central nervous system, extracellular glycine concentrations are regulated by two specific glycine transporters (GlyTs), GlyT1 and GlyT2. Here, we determined the relative transport activities and protein levels of GlyT1 and GlyT2 in membrane preparations from mouse brain stem and spinal cord at different developmental stages. We report that early postnatally (up to postnatal day P5) GlyT1 is the predominant transporter isoform responsible for a major fraction of the GlyT-mediated [(3)H]glycine uptake. At later stages (>>= P10), however, the transport activity and expression of GlyT2 increases, and in membrane fractions from adult mice both GlyTs contribute about equally to glycine uptake. These alterations in the activities and expression profiles of the GlyTs suggest that the contributions of GlyT1 and GlyT2 to the regulation of extracellular glycine concentrations at glycinergic synapses changes during development.
EVALuna2:4678